Involvement of PACLOBUTRAZOL RESISTANCE6/KIDARI, an Atypical bHLH Transcription Factor, in Auxin Responses in Arabidopsis - Zheng, Kaijie; Wang, Yating; Zhang, Na; Jia, Qiming; Wang, Xutong; Hou, Chunjiang; Chen, Jin-Gui; Wang, Shucai (Frontiers in Plant Science, 2017)
Auxin regulates nearly all aspects of plant growth and development, including cell division, cell elongation and cell differentiation, which are achieved largely by the rapid regulation of auxin response genes. However, the functions of a large number of auxin response genes remain uncharacterized. Paclobutrazol Resistance (PRE) proteins are non-DNA binding basic helix-loop-helix transcription factors that have been shown to involve in gibberellin and brassinosteroid signaling, and light responses in Arabidopsis. Here, we provide molecular and genetic evidence that PRE6, one of the six PRE genes in Arabidopsis, is an auxin response gene, and that PRE6 is involved in the regulation of auxin signaling. By using quantitative RT-PCR, we showed that the expression level of PRE6 was increased in response to exogenously applied IAA. GUS staining results also showed that the expression of GUS reporter gene in the PRE6p:GUS transgenic seedlings was elevated in response to auxin. Phenotypic analysis showed that overexpression of PRE6 in Arabidopsis resulted in auxin-related phenotypes including elongated hypocotyl and primary roots, and reduced number of lateral roots when compared with the Col wild type seedlings, whereas opposite phenotypes were observed in the pre6 mutants. Further analysis showed that PRE6 overexpression plants were hyposensitive, whereas pre6 mutants were hypersensitive to auxin in root and hypocotyl elongation and lateral root formation assays. By using protoplasts transfection, we showed that PRE6 functions as a transcription repressor. Consist with this, the expression of the auxin response reporter DR5:GUS was decreased in PRE6 overexpression lines, but increased in pre6 mutants. When cotransfected into protoplasts, ARF5 and ARF8 activated the expression of the PRE6p:GUS reporter. Chromatin immunoprecipitation assays showed that ARF5 and ARF8 can be recruited to the promoter regions of PRE6. Taken together, these results suggest that PRE6 is an auxin response gene who expression is directly regulated by ARF5 and ARF8, and that PRE6 is a transcription repressor that negatively regulates auxin responses in Arabidopsis.